The Assessment of Employee Engagement Level in A New Institution During Transition Period (Case Study: OJK) - kurnia, Reza; Welly, John (Journal of Business and Management, 2015)
Abstract-Engagement between the company and employees must be built to create the impulse for employees to work more optimally. Employee engagement can make more profit because the employees are not only thinking of themselves, but also they are trying to improve and develop where he works. Nowadays, OJK employees are in transition period or can be called also as temporary employees. The uncertainty of the employee as a permanent employee can be something risky for OJK. Therefore, OJK should attract the temporary employees that are in the transition period be more engage to company. This study aims for measure and determine the level of employee engagement in OJK using Aon Hewittâ€™s model. The sample used in this study is simple random sampling with the required total respondents amounted to 92 people. Distribution of the questionnaire addressed in accordance with the scope which is to the OJK employees from BI. To see the relationship of independent variables on the dependent variable, multiple linear regression method is used. The results of this research is the formed of new factor consist of six variables equal to the number of previous factors. These six factors have a very strongÂ relationship with the level of employee engagement. Then, there is an equation result from the regression method that used.Â Keywords: OJK, employee engagement, multiple linear regression, Aon Hewitt